The Strategy To Increase The Purchase Intention Of Unpacked Products - Dipa Mulia; Muchsin S. Shihab (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
Consumer orientation toward Green Products or environmentally friendly products is one of the supporting factors for business continuity. The Green Product in this study is a refill product without packaging (unpacked product). Consumer behaviour in choosing Green Products is part of Pro-Environmental Behavior (PEB) which is largely determined by several things. This study raises several aspects: knowledge, economics, supporting facilities, packaging of the product, and environmental attitude. This research involved 124 respondents who live in Jakarta and surrounding areas. The selection of respondents was carried out by purposive sampling method, with the criteria of respondents being groups of people who were aware of the existence of refillable products without packaging. Data analysis was carried out using Structure Equation Modeling – Partial Least Square (SEM-PLS). The research reveals that all independent variables have a significant effect except for economic aspects.